Digital Literacy Model through Critical Reading of Hoax News Texts with SQ3R Technique - Arifah, Zahira Nur; Oshmany, Muhammad Iqbal; Rahmawati, Dinda Putri; Priatna, Danar Dwi; Satria, Rakha; Kusmayati, Nurita Bayu (Balai Bahasa Kalimantan Tengah, 2024)
The reading literacy level of students is still low, while the level of internet use is high. The higher the use of the internet, the more open the opportunity for students to be consumed by hoax news. Therefore, this research aims to develop a digital literacy model through critical reading of hoax news texts with the SQ3R technique. The research method used is RD with ADDIE model stages. The population of this study is an A-accredited junior high school in East Jakarta. Phase D students at SMPN 20 Jakarta, SMPN 74 Jakarta, and SMP Diponegoro 1 Jakarta are samples of this research. The instruments used are questionnaires and interviews. Data analysis techniques use Likert scale and rating scale. Based on the analysis of validation data, the average validation percentage score of 89% which is categorized as very feasible to use, but there needs to be improvement according to validators. In addition, data analysis at the evaluation stage resulted in an average score of the percentage of responses from students to the learning model included in the good criteria with a percentage of 82%, while teachers rated the learning model included in the very good/very feasible criteria with a percentage of 91%.AbstrakTingkat literasi membaca peserta didik masih rendah, sedangkan tingkat penggunaan internet tinggi. Semakin tinggi penggunaan internet, semakin membuka peluang peserta didik termakan berita hoaks. Oleh karena itu, riset ini bertujuan mengembangkan sebuah model literasi digital melalui membaca kritis pada teks berita hoaks dengan teknik SQ3R. Metode riset yang digunakan ialah RD dengan tahapan model ADDIE. Populasi riset ini ialah SMP berakreditasi A di Jakarta Timur. Peserta didik fase D di SMPN 20 Jakarta, SMPN 74 Jakarta, dan SMP Diponegoro 1 Jakarta merupakan sampel riset ini. Instrumen yang digunakan yaitu angket dan wawancara. Teknik analisis data menggunakan skala Likert dan rating scale. Berdasarkan analisis data validasi, rata-rata skor persentase validasi sebesar 89% yang masuk kategori sangat layak digunakan, tetapi perlu ada perbaikan menurut validator. Selain itu, analisis data pada tahap evaluation menghasilkan rata-rata skor persentase respons dari peserta didik terhadap model pembelajaran masuk dalam kriteria baik dengan persentase 82%, sedangkan guru menilai model pembelajaran masuk dalam kriteria sangat baik/sangat layak dengan persentase 91%.